Truly madly magically - Beck, Hazel (Beck, Hazel. Witchlore, 2024)
"A witch cursed to tell the truth, and the man who won't let her lie to herself anymore... Cursed by her own mother to always tell the truth and one of the only half-witches around, Ellowyn Good has never considered herself an equal part of the Riverwood coven. But when the Joywood, the evil rules of the witching world, target her directly, she begins to wonder why they want her gone. She'll need to work with her newly formed coven to survive, which includes dealing with her first love, past wreckage and a whole new complication she didn't see coming. With their fates in the balance, Ellowyn will have to learn to trust Zander again - or be doomed to repeat the mistakes of the past. Assuming they all survive the Joywood's latest bid for absolute power over the witching world..." -- Back cover.